2016
DOI: 10.3389/fmicb.2016.00796
|View full text |Cite
|
Sign up to set email alerts
|

The Architecture of Iron Microbial Mats Reflects the Adaptation of Chemolithotrophic Iron Oxidation in Freshwater and Marine Environments

Abstract: Microbes form mats with architectures that promote efficient metabolism within a particular physicochemical environment, thus studying mat structure helps us understand ecophysiology. Despite much research on chemolithotrophic Fe-oxidizing bacteria, Fe mat architecture has not been visualized because these delicate structures are easily disrupted. There are striking similarities between the biominerals that comprise freshwater and marine Fe mats, made by Beta- and Zetaproteobacteria, respectively. If these bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
181
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 116 publications
(198 citation statements)
references
References 60 publications
15
181
0
2
Order By: Relevance
“…This suggests that DIS-1 is a good representative of natural FeOB capable of colonizing steel surfaces. The behavior of DIS-1 growing on the coupon surface is also reminiscent of stalk-forming FeOB that grow at hydrothermal vents and are related to DIS-1 (41). In this case, zetaproteobacteria also produce loosely adherent mats on the surfaces of basaltic lava substrata around the vents (11).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This suggests that DIS-1 is a good representative of natural FeOB capable of colonizing steel surfaces. The behavior of DIS-1 growing on the coupon surface is also reminiscent of stalk-forming FeOB that grow at hydrothermal vents and are related to DIS-1 (41). In this case, zetaproteobacteria also produce loosely adherent mats on the surfaces of basaltic lava substrata around the vents (11).…”
Section: Discussionmentioning
confidence: 91%
“…It is likely that this is the natural habitat of DIS-1. A recent study that captured intact vent mats showed stalk-forming FeOB were early colonizers and the primary architect of these mats (41). Stalk formation occurred in a highly parallel fashion, such that the mat grew with a uniform directionality perpendicular to the rock face and showed remarkable temporal and spatial coordination in the formation of the intact microbial mat (41).…”
Section: Discussionmentioning
confidence: 99%
“…These results are in good agreement with the optical microscopy results from the Jan Mayen Si‐Fe mounds, which show that the preferred orientation of irregular stalks is localized. Microbial mats in natural hydrothermal environments are affected by shifting flow paths and changing redox gradients during progressive Fe‐oxyhydroxide precipitation (Chan, McAllister, et al, ) and are sporadically exposed to strong fluid flow (Bernis, Lowell, & Farough, ). These factors likely impact the directionality of the filamentous fabric by promoting both abrupt and gradual changes in filament orientation, explaining the confinement of aligned filaments to distinct domains.…”
Section: Discussionmentioning
confidence: 99%
“…One common morphotype in mats that attaches to either sheaths or stalks is an organism that produces unique Y-shaped branched filaments (Chan et al, 2016). Since ferrous iron is assumed to be the primary energy source for both cosmopolitan and endemic strains, other traits may play a role in determining the successful ecological strategies of cosmopolitan Zetaproteobacteria.…”
Section: Exploring Zetaproteobacteria Diversitymentioning
confidence: 99%
“…The spatial resolution for collecting samples with the mat sampler was approximately 1 cm, either vertically or horizontally. Chemistry measurements were conducted using an in-situ electrochemical analyzer, ISEA, (ISEA-III, Analytical Instrument Systems, Flemington, NJ, USA) as described elsewhere (Chan et al, 2016). 1A).…”
Section: Study Overview Site Description and Samplingmentioning
confidence: 99%